2001
DOI: 10.1029/2000jd000055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of integrated cloud liquid and precipitable water vapor retrievals from microwave radiometers during the Surface Heat Budget of the Arctic Ocean project

Abstract: Abstract. We investigated a variety of factors that influence the determination of precipitable water vapor (V) and integrated cloud liquid (L) by dual-channel microwave radiometers (MWRs). These factors include radiometric calibration; dry, water vapor, and liquid absorption coefficients; and physical versus statistical retrieval methods. We then applied the analysis to the MWR that was operated by the Atmospheric Radiation Measurement Program (ARM) during the Surface Heat Budget of the Arctic Ocean project. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
152
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(157 citation statements)
references
References 23 publications
5
152
0
Order By: Relevance
“…Although there are 5-years of data used per month, these distributions should be regarded as rough estimates of the month-to-month differences in LWP. This is because recent research has found that MWR uncertainties exist in the LWP retrievals that limit the attainable accuracy to between 20-30 g m À2 [Liljegren and Lesht, 1996;Westwater et al, 2001;Marchand et al, 2003;Turner et al, 2007], which represents a large uncertainty compared to many of the values shown. Still the shift shown, from smaller to larger LWP from March through June, is consistent with climatological considerations that optically thinner stratiform cloud tend to occur in spring versus summer [e.g., Leontyeva and Stamnes, 1994].…”
mentioning
confidence: 99%
“…Although there are 5-years of data used per month, these distributions should be regarded as rough estimates of the month-to-month differences in LWP. This is because recent research has found that MWR uncertainties exist in the LWP retrievals that limit the attainable accuracy to between 20-30 g m À2 [Liljegren and Lesht, 1996;Westwater et al, 2001;Marchand et al, 2003;Turner et al, 2007], which represents a large uncertainty compared to many of the values shown. Still the shift shown, from smaller to larger LWP from March through June, is consistent with climatological considerations that optically thinner stratiform cloud tend to occur in spring versus summer [e.g., Leontyeva and Stamnes, 1994].…”
mentioning
confidence: 99%
“…The radiative characteristics of marine stratocumulus are closely tied to cloud fraction, which differs dramatically between regions of continuous unbroken cloud versus regions with mesoscale pockets of open cells (Stevens et al, 2005). Observational and modeling studies have implicated heavy drizzle cells in the transitions between closed-and open-cell mesoscale cloud structures (Stevens et al, 2005;van Zanten and Stevens, 2005;Comstock et al, 2007;Savic-Jovic and Stevens, 2008;Wang and Feingold, 2009;Wood et al, 2011a). These studies suggest that drizzle is a necessary but not sufficient condition for the formation of pockets of open cells.…”
Section: Introductionmentioning
confidence: 90%
“…C-band Z > 0 dBZ is approximately equivalent to LWP ≈ 200 g m −2 (Wood et al, 2011a). This definition corresponds to the subset of drizzle features within marine stratocumulus with sufficiently high drizzle intensity that precipitation usually reaches the surface .…”
Section: Binary Heavy Drizzle Cell Classification Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The monthly means of the cloud liquid and ice water paths (IWPs) are calculated from the original data of 1-min resolution provided by M. Shupe. Liquid water paths are derived from the microwave radiometer brightness temperatures at 31.4-GHz frequency (the "liquid" channel insensitive to water vapor or ice), yielding retrievals with 25 g m Ϫ2 accuracy (Han and Westwater 1995;Westwater et al 2001). The data are available from 6 December 1997 until 9 September 1998.…”
Section: Observational Datamentioning
confidence: 99%